Analisis Intensi Penggunaan Internet Banking Syariah Di Kalangan Dosen - Harahap, Enni Eriani; Lubis, Delima Sari; Fauzan, M (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2024)
Internet Banking is a service that allows bank customers to carry out banking transactions via the internet. This can be done through an application that can be accessed on the website by customers. Internet Banking has advantages and disadvantages. One of the main drawbacks is the need for a smartphone device and a reliable internet connection. Security is also an important issue, with the risk of fraud and potential problems if a smartphone is lost or stolen. However, the benefits are very large, including checking balances, transfers between individuals and banks, as well as paying electronic bills such as electricity, credit, internet packages, and others. By using internet banking transactions are very practical. With internet banking, banking transactions such as fund transfers, bill payments and balance checks anytime and anywhere without having to go to a physical bank. This really helps save time and energy. Internet banking makes it easy to manage finances. I can quickly track transaction history and easily compile personal financial reports. Therefore, have very positive intentions in using internet banking. The method used in this research is a quantitative method based on the philosophy of positivism and functions to examine a certain population or sample by collecting data using research instruments. This type of research is field research, namely direct research carried out in the field or on respondents to obtain information through interviews or questionnaires. Data collection instruments in this research are Questionnaires, Documentation, Testing Instruments in this research are Validity and Reliability, Data Analysis Techniques in this research are Designing a Measurement Model (Outer Model), Designing a Structural Model (Inner Model) and Hypothesis Testing. The results of the analysis from this discussion are that Performance Expectancy has a significant and influential effect on the use of Internet Banking among lecturers. Effort Expectancy has a significant and influential effect on the use of Internet Banking among lecturers. Social Influence (Self Confidence) has an influence and is not significant on the use of Internet Banking among lecturers. Facilitating Conditions have a significant and significant influence on the use of Internet Banking among lecturers. Self Efficacy (Self Confidence) has a significant influence on the use of Internet Banking among lecturers. Hedodic Motivation (Satisfaction Factor) has a significant influence on the use of Internet Banking among lecturers. Price Value (Price Factor) has a significant influence on the use of Internet Banking among lecturers.